Školj Castle and its architectural history - Sapač, Igor (Annales. Series historia et sociologia, 2015)
On one of the highest rocky ledges above the Reka River, just a few kilometers from Famlje Village and near Škocjan Caves, Školj Castle is today one of the less known castles in Slovenia. For more than a century the castle is abandoned. Until the 19th century it was among the most interesting castles in Carniola because of its picturesque location and architectural design. In this article we present the results of the last architectural history research, based on study of written archive sources, literature, image sources and castle ruins. The results show the castle's importance, that it could be possible and would be necessary to preserve and to restore his remains.
Keywords: arhitekturna zgodovina; grad Školj; gradovi; Slovenia; Slovenija; stavbna dediščina